Global risk factors - Rogov, Mikhail A. (Journal of Business Economics and Management, 2006)
The paper deals with a problem of solar and geomagnetic activity as global risk factors in financial risk management. The history of the idea of solar – earth relations is rather long (Hershel, 1804; Jevans, 1870 – Theory of Solar cycles, Chizhevsky, 1920 ‐ Theory of Heliotaraxy; Collins, 1965 etc.), but financial risk management does not use these facts really and this paper may help to demonstrate some new risk management tools based on new results of the author’s studies (Rogov 2003). First published online: 14 Oct 2010